Achieving holistic, quality-of-life focused care: description of a Compassion Care Community initiative in Canada. (5th July 2022) - Howard, Michelle; Pfaff, Kathryn; Sattler, Deborah; Dolovich, Lisa; Marshall, Denise; Zwarenstein, Merrick; Upshur, Ross
Abstract: The compassionate community movement as both a public health approach and a social model of care for various life stages is gaining traction in Canada and elsewhere. One example is the Windsor-Essex Compassion Care Community (WECCC), an evidence-based model and set of tools to improve the quality of life, health and wellness of vulnerable and aging populations by identifying and addressing upstream and downstream social and other risks to physical and mental health. This paper presents findings from the WECCC pilot evaluation. The WECCC initiative provided one-on-one volunteer-supported quality of life assessment, resource navigation and goals support program (Catalyzing Community Connections). This was augmented with public education sessions on social connection and loneliness (Importance of Being Connected) for the broader population. The RE-AIM framework was used to frame evaluation of WECCC through the first 4 years. Questionnaires were used to evaluate participant outcomes related to implementation and effectiveness. Interviews and focus groups were completed to understand impacts. From 2017 to 2020, WECCC has engaged over 2, 500 individuals, 65 organizations and 400 volunteers combined in both programs. Nearly all (82% to 95%) participants reported positive changes to health, quality of life and/or social connections. This developmental phase of a compassionate community initiative has allowed piloting of an evaluation framework focusing on reach, adoption, implementation and early signals of effectiveness and maintenance. This demonstration provides information on feasibility, acceptability and potential impacts of this type of over-arching community initiative. Lay Summary: The compassionate communities movement is a social and holistic approach to care that engages community members in caring for others. The movement is growing around the world. The philosophy is that all citizens benefit from participating in care for others who are aging, disabled, nearing end-of-life or struggling with determinants of health. The Windsor-Essex Compassion Care Community (WECCC) is a Canadian example of this model. WECCC seeks to improve the health of people at any stage of life by helping them to identify their life needs and goals and providing them support to meet them. The program has two core components: one-on-one volunteer-support for person-directed goals and navigation (Catalyzing Community Connections) and public education sessions about loneliness and social connection (Importance of Being Connected). Evaluation is a routine part of program delivery with questionnaires, interviews and focus groups used to understand the program's outcomes. From 2017 to 2020, WECCC has worked with over 2, 500 individuals, 65 organizations and 400 volunteers. Satisfaction with the program is very high (95%). Nearly all participants reported positive changes to their quality of life (82%) and social connections (95%). Although pilot results are favorable, continued evaluation and stronger research designs are needed to comprehensively evaluate the WECCC program over time and to support growth and spread of the model.